L’Epistola 70 di Cipriano di Cartagine in versione etiopica - Bausi, Alessandro (Aethiopica, 1998)
Ethiopic literary tradition numbers hagiographical and magical texts centred on the legendary figure of St. Cyprian the magician, but no Ethiopic version of St. Cyprian’s (bishop of Carthage, † 258 A.D.) works has so far been registered in the current literature. This contribution is devoted to the edition, translation, and philological analysis of the only authentically cyprianic text preserved in Ethiopic: Epistula 70. This «synodal epistle» (254 or 255 A.D.) originates from 3rd century baptismal controversies: Cyprian maintains that it is necessary that all who come from heresy must receive full baptism. Besides the Latin original text, Epistula 70 is preserved in a Greek translation (inserted in Zonara’s and Balsamon’s canonical collections), but no oriental version exists, except for the Ethiopic one. Epistula 70 is preserved in 5 mss. of the Ethiopic Sēnodos: EMML 1843, ff. 58rb–60rb; EMML 2430, ff. 42rc–43rb; BN Zotenberg 121 [Éth. 95], ff. 78va–79va; BAV, Borgiano etiopico 2, ff. 173rb–174vb; Uppsala, University library, O Etiop. 39, ff. 121ra–122rc; the 5 mss. can be classified according to a clear stemma codicum and all of them have been used in the present edition. J.M. Wansleben identified Epistula 70 in 1671, but his discovery has remained neglected till now. Concerning the Vorlage of the Ethiopic translation, there are some clues to a direct dependence on a Greek version, which could be older than that preserved in the byzantine canonical collections.